2006
DOI: 10.1016/j.brainres.2006.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and predictability effects on event-related potentials during reading

Abstract: Effects of frequency, predictability, and position of words on event-related potentials were assessed during word-by-word sentence reading in 48 subjects in an early and in a late time window corresponding to P200 and N400. Repeated-measures multiple regression analyses revealed a P200-effect in the high-frequency range; also the P200 was larger on words at the beginning and end of sentences than on words in the middle of sentences (i.e., a quadratic effect of word position). Predictability strongly affected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
253
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 253 publications
(307 citation statements)
references
References 55 publications
35
253
5
Order By: Relevance
“…This finding adds further support to the claim that phonological activation occurs early enough to affect lexical access. Indeed, Hauk and Pulvermüller (2004) also reported word frequency effects in a very similar time window between 150 and 200 ms (see also Assadollahi and Pulvermüller, 2001;Sereno, Brewer, O'Donnell, 2003;Dambacher et al, 2006, but see Polich and Donchin, 1988;Van Petten and Kutas, 1990;Rugg, 1990;Pulvermüller et al, 2001 for later effects of word frequency). Finally, Hauk et al (2006a) reported lexical and semantic processing as early as 160 ms employing linear regression analysis on neurophysiological data from a visual lexical decision task.…”
Section: Early Phonological Activation In Visual Word Recognitionmentioning
confidence: 86%
See 1 more Smart Citation
“…This finding adds further support to the claim that phonological activation occurs early enough to affect lexical access. Indeed, Hauk and Pulvermüller (2004) also reported word frequency effects in a very similar time window between 150 and 200 ms (see also Assadollahi and Pulvermüller, 2001;Sereno, Brewer, O'Donnell, 2003;Dambacher et al, 2006, but see Polich and Donchin, 1988;Van Petten and Kutas, 1990;Rugg, 1990;Pulvermüller et al, 2001 for later effects of word frequency). Finally, Hauk et al (2006a) reported lexical and semantic processing as early as 160 ms employing linear regression analysis on neurophysiological data from a visual lexical decision task.…”
Section: Early Phonological Activation In Visual Word Recognitionmentioning
confidence: 86%
“…There is evidence for very early lexical processing at around 100 ms after stimulus presentation (e.g., Pulvermüller et al, 2001;Sereno et al, 1998;, although most studies locate lexical access later at around 250 ms (e.g., Cohen, et al, 2000;Grainger et al, 2006;Nobre et al, 1994). The earliest effects of word frequency were found at around 130 ms (e.g., Assadollahi and Pulvermüller, 2001;Sereno et al, 1998Sereno et al, , 2003Dambacher et al, 2006), but the majority of studies locate it later, at around 300 ms (e.g., Polich and Donchin, 1988;Van Petten and Kutas, 1990).…”
Section: The Present Studymentioning
confidence: 99%
“…Sereno, Rayner and Posner (1998) reported a larger N1 with a concurrent left anterior positivity for low frequency (LF) than for high frequency (HF) words 132-192 ms after the stimulus onset. More negative amplitudes for LF than for HF words were observed by Proverbio, Vecchi and Zani (2004) at 150-190 ms, and at 140-200 ms by Dambacher, Kliegl, Hofmann and Jacobs (2006). King and Kutas (1998) observed what they refer to as "frequency sensitive negativity" (FSN), which has a left frontal topography and peaks at ~280 ms for HF and ~335 ms for LF words.…”
Section: The Experimentsmentioning
confidence: 99%
“…Several ERP studies documented differential activation for low and high frequency words within the first 200 ms after presentation, suggesting that lexical processing relies indeed on the rapid bottom-up flow of visual properties (Braun, Hutzler, Ziegler, Dambacher, & Jacobs, 2009;Dambacher, Kliegl, Hofmann, & Jacobs, 2006;Hauk, Davis, Ford, Pulvermüller, & MarslenWilson, 2006;Hauk & Pulvermüller, 2004;Penolazzi, Hauk, & Pulvermüller, 2007;Sereno, Brewer, & O'Donnell, 2003;Sereno, Rayner, & Posner, 1998). …”
Section: The Role Of Presentation Ratementioning
confidence: 99%